2014
DOI: 10.1115/1.4027128
|View full text |Cite
|
Sign up to set email alerts
|

Flame Structure Effects at High G-Loading

Abstract: Previous research has been conducted showing significant benefits on combustion effi ciency and stability by creating high gravity-loaded combustion environments. Ultracom pact combustor systems decrease the size and weight of the overall engine by integrating the compressor, combustor, and turbine stages. In this system, the core flow is split and a portion is routed into a circumferential direction to be burned at a high equivalence ratio. Fuel and air are brought into the cavity and combusted in a high g-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The superior combustion performance of high- g technology has motivated many researchers to conduct experiments to verify this phenomenon, and numerous studies have been conducted to obtain a more detailed flame mechanism through simulations. Recently, researchers have pointed out that the high- g combustion mechanism is more complex and may be related to the Rayleigh–Taylor instability. Briones et al reproduced Lewis’s experiments using a two-dimensional computational domain to simulate a rotating combustion tube and found that higher values of g -loading were not better, and at larger values of g -loading, the flame front broke up and disrupted its own mixing with the fuel, which led to localized quenching and slowed down flame propagation. Briones proposed that Rayleigh–Taylor instability affects the localized flow rate of the flame and thus the flame propagation rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superior combustion performance of high- g technology has motivated many researchers to conduct experiments to verify this phenomenon, and numerous studies have been conducted to obtain a more detailed flame mechanism through simulations. Recently, researchers have pointed out that the high- g combustion mechanism is more complex and may be related to the Rayleigh–Taylor instability. Briones et al reproduced Lewis’s experiments using a two-dimensional computational domain to simulate a rotating combustion tube and found that higher values of g -loading were not better, and at larger values of g -loading, the flame front broke up and disrupted its own mixing with the fuel, which led to localized quenching and slowed down flame propagation. Briones proposed that Rayleigh–Taylor instability affects the localized flow rate of the flame and thus the flame propagation rate.…”
Section: Introductionmentioning
confidence: 99%
“…The superior combustion performance of high- g technology has motivated many researchers to conduct experiments to verify this phenomenon, 12 14 and numerous studies have been conducted to obtain a more detailed flame mechanism through simulations. 15 18 Recently, researchers have pointed out that the high- g combustion mechanism is more complex and may be related to the Rayleigh–Taylor instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation